Gender Inequality and Female Sports Participation in Turkey - Meltem Ince Yenilmez (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
Research Questions: Discrimination remains a sore point for women in Turkish sports. This has subsequently hindered women from participating or building thriving careers in sports in Turkey. Many women are discouraged from taking part in professional sports due to the perceptions existing around such activities. Therefore, the Turkish female sports sector is growing at a very sluggish pace. The present study evaluates Turkish women's roles regarding connections between sports and politics to revolutionize the country. This assessment is vital to understand the barriers to Turkish women's sports participation and what can be done to encourage more women to invest in professional sports. Research Methods: The present study provides an in-depth view of the limiting factors hindering women from developing thriving professional Turkish sports careers. The research utilizes a semi-structured questionnaire to establish data from about 162 female participants (amateur and professional sportswomen) in different cities across the country. Results and Findings: The present study highlights that unequal salaries, unavailability of sports facilities for women, media misrepresentation, and pressures from the family, are some of the factors limiting the participation of females in Turkish sports. Inferences: The study provides insights on the vitality of sports programs and physical activities, everyone, including females. The study further emphasizes the need to create enabling environments that will foster female participation in Turkey's sports.